1997
DOI: 10.1111/j.1440-1827.1997.tb04525.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase (gelatinase) in T1 adenocarcinoma of the lung

Abstract: The expression of matrix metalloproteinase-2 (MMP-2; 72 kDa type IV collagenase/gelatinase A) and MMP-9 (92 kDa type IV collagenase/gelatinase B) was immunohistochemically investigated in 79 T1 adenocarcinomas of the lung using non-commercial polyclonal anti-MMP-2 and -9 antibodies. Thirty-two (41%) and 22 (28%) among the 79 cases were positive in the tumor cells for MMP-2 and -9, respectively. The incidences of MMP-2 and -9 immunoreactivities were higher (64 and 45%, respectively) in poorly differentiated tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 37 publications
3
67
0
2
Order By: Relevance
“…Expression of MMP-2 and MMP-9 is elevated in carcinomas in association with low differentiation grade and accelerated tumour progression in oral carcinoma, 30 lung adenocarcinoma, 31 bladder 32 and ovarian carcinoma 33 and papillary thyroid carcinoma. 34 MMP-2 expression correlates also with advanced disease in neuroblastoma.…”
Section: Mmps In Malignant Transformation and Cancer Progressionmentioning
confidence: 99%
“…Expression of MMP-2 and MMP-9 is elevated in carcinomas in association with low differentiation grade and accelerated tumour progression in oral carcinoma, 30 lung adenocarcinoma, 31 bladder 32 and ovarian carcinoma 33 and papillary thyroid carcinoma. 34 MMP-2 expression correlates also with advanced disease in neuroblastoma.…”
Section: Mmps In Malignant Transformation and Cancer Progressionmentioning
confidence: 99%
“…[19][20][21] Earlier studies have reported lower frequencies of MMP2 expression in bronchioloalveolar carcinomas. Kodate et al 19 showed that two of 11 cases (18%) of bronchioloalveolar carcinoma expressed MMP2, and that one of 11 cases expressed MMP9. Kitamura et al 20 reported eight of 48 cases (17%) of lung adenocarcinoma expressed MMP2 in the lepidic growth areas.…”
Section: Discussionmentioning
confidence: 96%
“…22 We anticipated that a bronchioloalveolar carcinoma would have little MMP mRNA and minimal gelatinolytic activity, as reported in earlier immunohistochemical studies. 19,20 Surprisingly, in situ hybridization showed that bronchioloalveolar carcinomas had significant amounts of mRNA for MMP2, MMP9, MT1-MMP, and TIMP2. In four cases of bronchioloalveolar carcinoma, the gelatinolytic activity was sufficient to destroy the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of these enzymes by cancer cells has been found to be correlated with the malignant potential of various cancers (30 -36). Expression of these enzymes may be responsible for tumor invasion and metastasis of T1 adenocarcinoma of the lung (37). We are currently investigating correlations between expression of these enzymes and BM preservation in the same specimens.…”
Section: Bm Preservationmentioning
confidence: 99%